Early, very high-titre convalescent plasma therapy in clinically vulnerable individuals with mild COVID-19: an international, randomised, open-label trialResearch in context - Simone Hoffmann; Eva Schrezenmeier; Maxime Desmarets; Fabian Halleck; Antoine Durrbach; Lynn Peters; Anna-Teresa Tremmel; Alina Seidel; Marita Führer; Friederike Bachmann; Jens Schrezenmeier; Jochen Greiner; et al. (EBioMedicine)
Summary: Background: COVID-19 convalescent plasma (CCP) is a treatment option for COVID-19. This study investigated the safety and efficacy of early, very high-titre CCP in immunocompromised individuals with mild COVID-19. Methods: This randomised, controlled, open-label trial assessed CCP in immunocompromised patients (n = 120) with mild COVID-19 in 10 clinical trial centres across Germany, France, and the Netherlands. Patients were randomised 1:1 to receive either standard of care (SoC) alone (SoC group) or SoC and 2 units of CCP. Most patients (89.7%) had received ≥3 SARS-CoV-2 vaccinations. The primary endpoint was hospitalisation for progressive COVID-19 symptoms or death by day 28 after randomisation, analysed on a modified intention-to-treat basis (117 patients). The safety analysis included the full analysis set. The trial is registered with EudraCT 2021-006621-22, and ClinicalTrials.gov, NCT05271929. Findings: Between April 11, 2022 and November 27, 2023, 120 patients were enrolled. Patients in the CCP group received a median of 559 ml CCP from convalescent, vaccinated donors with very high levels of SARS-CoV-2 antibodies (median 81,810 IU/ml) at a median 4 days after symptom onset. The primary outcome occurred in 5/58 patients (8.6%) in the SoC group and in 0/59 patients (0%) in the CCP group, difference −8.6% (95% confidence interval of difference −19% to −0.80%; p-value 0.027; Fisher's exact test). The course of SARS-CoV-2 antibodies in the patients demonstrated a passive transfer of antibodies by the CCP, in particular neutralising effects against new SARS-CoV-2 variants. Whole genome sequencing of SARS-CoV-2 in patients during follow-up showed significant intra-host viral evolution, but without differences between groups. CCP was well tolerated. Interpretation: Early administration of high-titre CCP can prevent hospitalisation or death in immunocompromised patients with mild COVID-19. Funding: Support-e project (European Union's Horizon 2020 Programme), German Federal Ministry of Education and Research, ZonMw, the Netherlands Organisation for Health Research and Development.